2021
DOI: 10.1016/j.jtho.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib Plus Gefitinib as First-Line Treatment in Advanced EGFR-Mutant NSCLC: The Phase III ACTIVE Study (CTONG1706)

Abstract: are two individuals with the same name.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 53 publications
1
127
3
Order By: Relevance
“…In addition, phase II and III trials have shown that apatinib plus gefitinib as first-line therapy resulted in superior PFS to placebo plus gefitinib in advanced EGFR-mutant NSCLC. Combination therapy resulted in more adverse events but did not interfere with the quality of life of patients (39,42).…”
Section: Lung Cancermentioning
confidence: 91%
“…In addition, phase II and III trials have shown that apatinib plus gefitinib as first-line therapy resulted in superior PFS to placebo plus gefitinib in advanced EGFR-mutant NSCLC. Combination therapy resulted in more adverse events but did not interfere with the quality of life of patients (39,42).…”
Section: Lung Cancermentioning
confidence: 91%
“…Several studies demonstrated that apatinib plus EGFR-TKIs (gefitinib) exhibited a tolerable safety profile and encouraging antitumor activity for advanced EGFRmutant NSCLC [52][53][54]. Thus, the efficacy of apatinib in EGFR-mutant NSCLC might be related with the inactivation of STAT3.…”
Section: Discussionmentioning
confidence: 99%
“…However, the above-mentioned studies were conducted without knowing EGFR mutation status. For patients with EGFR mutation, multiple studies had demonstrated that antiangiogenic agents plus EGFR-TKIs significantly improved PFS compared with EGFR-TKIs alone ( 80 84 ). Were similar results obtained in EGFR-mutated patients with TP53 concurrent mutations?…”
Section: Clinical Implications In Advanced Egfr-mutated Nsclc Patient...mentioning
confidence: 99%